The Influence of Workload and Work Stress Through Work Motivation as a Mediator on Employee Performance - Denny Astanto; Hendra Irawan (CV Pena Jaya Pers, 2025)
High performance will make employees more loyal to the organization, more motivated, work with feelings of pleasure and more importantly can increase the possibility of achieving high productivity. Work-related stress is known to exist and is a common and detrimental problem for workers. Workload is one aspect that must be considered by every organization, because workload is one of the factors that affect employee performance, so motivation is needed to reduce workload and work stress. The purpose of this study was to examine and analyze the effect of work stress, workload on employee performance with motivation as a mediator/intervening. The methodology used in this study is a quantitative approach research using multiple linear regression analysis and path analysis, this study involved 40 employees of gas stations 54.611.04 Gresik. The result is that workload and work stress have an insignificant effect on performance, while motivation as workload, work stress, motivation has a significant effect on employee performance at gas stations 54.611.04 Gresik.